2016
DOI: 10.1128/aac.02626-15
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Adherence to Oral Antibiotics and Postdischarge Clinical Outcomes among Patients Hospitalized with Staphylococcus aureus Skin Infections

Abstract: e Skin and soft tissue infections are common and frequently recur. Poor adherence to antibiotic therapy may lead to suboptimal clinical outcomes. However, adherence to oral antibiotic therapy for skin and soft tissue infections and its relationship to clinical outcomes have not been examined. We enrolled adult patients hospitalized with uncomplicated skin and soft tissue infections caused by Staphylococcus aureus who were being discharged with oral antibiotics to complete therapy. We fit the participants' pill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 39 publications
(57 reference statements)
1
46
1
1
Order By: Relevance
“…In addition, a recent article measuring the postdischarge adherence to oral antibiotics by an electronic bottle cap that recorded each pill bottle opening demonstrated a significant difference between self-reported adherence and electronically measured adherence (57% versus 96%; P Ïœ 0.0001) (12). In this study, poor adherence was associated with a lower clinical response at 30 days.…”
Section: Abstract Bone and Joint Infections Dalbavancin Osteomyelitmentioning
confidence: 46%
“…In addition, a recent article measuring the postdischarge adherence to oral antibiotics by an electronic bottle cap that recorded each pill bottle opening demonstrated a significant difference between self-reported adherence and electronically measured adherence (57% versus 96%; P Ïœ 0.0001) (12). In this study, poor adherence was associated with a lower clinical response at 30 days.…”
Section: Abstract Bone and Joint Infections Dalbavancin Osteomyelitmentioning
confidence: 46%
“…Due to the retrospective nature of this study, we were unable to assess adherence in either group. Adherence to PO antibiotics when measured using the Medication Event Monitoring System (Aprex, Union City, CA, USA) was reported to be between 18% and 57% . In comparison, adherence to antibiotics for patients receiving outpatient parenteral antibiotic therapy (OPAT) is consistently at or above 80% …”
Section: Discussionmentioning
confidence: 99%
“…Adherence to PO antibiotics when measured using the Medication Event Monitoring System (Aprex, Union City, CA, USA) was reported to be between 18% and 57%. [21][22][23] In comparison, adherence to antibiotics for patients receiving outpatient parenteral antibiotic therapy (OPAT) is consistently at or above 80%. 24,25 A study including 333 patient in the Veterans Administration system reported that 87% of patients who were defined as homeless successfully completed a defined course of parenteral antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that the compliance of patients depends on various factors and is often low [41], [42], [43]. For example, Eells et al state that patient adherence to oral antibiotic therapy for SSTI after hospital discharge was only 57 percent, which was associated with poor clinical outcomes [43]. Thus, a single-dose intravenous Dalbavancin is an option for patients where the LOS can be significantly reduced.…”
Section: Discussionmentioning
confidence: 99%